Peranan Advokat Sebagai Konsultan Hukum Dalam Penegakan Hukum Pidana di Indonesia Perspektif Undang-Undang Nomor 18 Tahun 2003 - Zulfan Baihaqi; M. Ridho Hakim; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Article 5 of the law of the Republic of Indonesia Number 18 of 2003 concerning Advocates has regulated the existence of Advocates as law enforcers. Law enforcement is a must for the state to protect its citizens, because law enforcement is upholding the values ​​of truth and justice. Efforts to tackle crime with criminal law are essentially part of criminal law enforcement efforts. Criminal law enforcement is realized through a legal policy that is part of national legal politics. This involves various elements within the state, from legislators, law enforcement officials, to citizens. The role of advocates as professionals who are free, independent and responsible as legal consultants in relation to the implementation of criminal law. such as police and prosecutors. Criminal law is one of the pillars in maintaining the rule of law. Therefore the purpose of this writing is to find out and analyze the role of advocates in enforcing criminal law in Indonesia as in the advocacy law, namely Number 18 of 2003. The writing method used is the normative juridical method. The normative juridical method is library law research which is carried out by examining library materials or mere secondary data. The data collection method itself uses primary data research methods. Primary data was obtained from empirical research on research informants who were considered relevant and representative. Data collection procedures were carried out through library research. Keywords: Advocate, Law Enforcement, Legal Consultant